Pain management in hospitalized children: unveiling barriers from the nursing perspective - Danton Matheus de Souza; Giovanna Sanches Lestinge; Joese Aparecida Carvalho; Lisabelle Mariano Rossato (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand nursing team perceptions about the barriers in pain management in the care of hospitalized children. Method: Descriptive-exploratory study, with a qualitative approach, conducted with eight nurses and seven nursing technicians. Data were collected at the Universidade de São Paulo University Hospital, between June and September 2022, through individual interviews, analyzed from the perspective of thematic content analysis and in the light of Symbolic Interactionism. Results: The following categories emerged: 1) Knowledge translation: is pain management actuallyperformed? and 2) Reflecting changes: how to achieve the potential of pain management? Professionals have theoretical knowledge about pain management, however, they listed numerous barriers at each stage, mainly related to institutional routine, and, when reflecting on this context, they indicated the need for an institutional protocol. Final considerations: Barriers stand out from theoretical knowledge and make pain management for hospitalized children disregarded. Knowing this context is relevant forimplementing change strategies.